Water - Swallow, Su. (New York : F. Watts, 1990)
Describes the water cycle, plants and animals that live in water, hydropower, and associated water customs, festivals, and activities.
Includes index.
Booklist.
4.0
K-3
Keywords: Water -- Juvenile literature; Water; Water; Water